Annotated bibliography on medical and veterinary entomology in the Philippines - Ricaforte, Ella T. (Institute of Library Science, University of the Philippines Diliman, 1978)
This annotated bibliography is a compilation of research studies and literature on medical and veterinary entomology common to the Philippines from 1930-1975. It is arranged by arthropod groups and alphabetically by author under each group. Each entry is numbered consecutively from 001-504. No indexing by scientific name is made unless contained in the title or whenever the title is vague.